2010
DOI: 10.1016/j.jcrs.2009.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of transepithelial crosslinking (C3-R/CXL)

Abstract: We appreciate having another chance to point out that corneal CXL is a clinical procedure with complications and failures, and we are grateful that Kymionis et al. drew attention to more infrequent complications that were not mentioned in our discussion.We fully agree that an impact on the cornea such as CXL may initiate a recurrence of herpes keratitis and in cases with an ocular herpes history, systemic antimetabolite therapy is clearly indicated. Stimulation of an inflammatory reaction such as diffuse lamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 5 publications
0
31
0
1
Order By: Relevance
“…3 Complications such as severe bacterial keratitis, viral reactivation of herpes keratitis, and sterile infiltrates have been reported. [4][5][6] To avoid such complications, Boxer Wachler et al 7 suggested modifying the technique by keeping the epithelium intact (epithelium-on or transepithelial CXL).…”
mentioning
confidence: 99%
“…3 Complications such as severe bacterial keratitis, viral reactivation of herpes keratitis, and sterile infiltrates have been reported. [4][5][6] To avoid such complications, Boxer Wachler et al 7 suggested modifying the technique by keeping the epithelium intact (epithelium-on or transepithelial CXL).…”
mentioning
confidence: 99%
“…Boxer Wachler et al 13 argue that the use of preservative-based anesthetic drops is a decisive feature for the success of transepithelial CXL. Benzalkonium chloride (BAC) can loosen the tight junctions of the corneal epithelial cells, increasing permeability for riboflavin and allowing CXL without removal of the epithelium.…”
mentioning
confidence: 99%
“…5 The collection of large amounts of data and their critical evaluation are needed, as the future of many young patients will be affected. Collaboration, or at least reciprocal recognition, between research groups is essential.…”
Section: Transepithelial Crosslinkingmentioning
confidence: 99%